1980-1990 ЖЫЛДАРДАҒЫ ЕГИПЕТТІҢ САЯСИ ӨМІРІНДЕГІ ӨЗГЕРІСТЕР - Жанатаева, К. Б. (Journal of Oriental Studies, 2016)
В этой статье рассматривается изменения политической жизни Египта, борьбы политической партий 80-90-х гг. ХХІ века.This article is dedicated to the changes in political life of Egypt, the struggle of political parties in 1980-1990-s of twenty-first century.